ELEFAN-based population dynamics of yellowlined goatfish Upenaeus sulphureus from the Bay of Bengal - Mustafa, MD Golam (Indian Journal of Fisheries, 2011)
Upellaeus sulphureus is the most abundatil among the goatfish species available in the northern Bay of Bengal of Bangladesh. This species usually moves in schooL It forms a considerable part of the demersal fishery and accounts for 3Â°/.) of the total biomass.